Do Inclusive Growth Strategies Affect Corporate Financing Policy? Evidence from The Metal and Mining Sector - AkhmetovAlexander; KhamidullinaMaria (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2023)
The influence of inclusive growth strategy on corporate financing policies is examined within the metals and mining industry. A dataset comprises 212 of the largest publicly traded companies observed from 2016 to 2021. An econometric analysis revealed no significant effect of inclusion indicators on the financing policies of these companies. However, a positive association between the corporate resource efficiency and leverage levels was observed. Though no single inclusion indicator influences the volume of sustainable financing, the indicator of human rights compliance positively impacts the number of such financing arrangements. Furthermore, only the levels of emission reduction and the extent of improvement in living standards of local communities significantly influence the cost of capital (with a positive dependence for the former, and a negative dependence for the latter). Inclusion indicators have little impact on the capital structure, with leverage levels largely determined by metals pricing dynamics. Higher levels of inclusion correlate with increased utilization of sustainable financing. The findings can be used when implementing inclusive growth strategies in the metals and mining industry as well as when deciding on the financing of projects within this sector. We believe that analysis of other industries and a longer period of time, different results may be obtained. This is, on the one hand, a limitation of this work, and on the other hand, an area for further research.